Affecting future individuals: Why and when germline genome editing entails a greater moral obligation towards progeny. (2nd April 2021) - Battisti, Davide
Abstract: Assisted reproductive technologies have greatly increased our control over reproductive choices, leading some bioethicists to argue that we face unprecedented moral obligations towards progeny. Several models attempting to balance the principle of procreative autonomy with these obligations have been proposed. The least demanding is the minimal threshold model (MTM), according to which every reproductive choice is permissible, except creating children whose lives will not be worth living. Hence, as long as the future child is likely to have a life worth living, prospective parents may be allowed to use preimplantation genetic diagnosis (PGD) to select embryos with genetic diseases or disabilities. Assuming a consequentialist person‐affecting view of morality, this paper investigates whether the MTM is an appropriate tool to guide procreative decisions given the continuous development of reproductive genetic technologies. In particular, I consider germline genome editing (GGE) and I argue that its application in human reproduction, unlike PGD, should be conceived as person‐affecting towards future progeny. I claim that even if we assume the plausibility of the MTM within PGD, we are committed to accepting that a greater moral obligation towards progeny should guide procreative decisions if GGE were available. In this case, the MTM should no longer be considered an appropriate instrument to guide procreative choices. Finally, I investigate when we face this greater moral obligation, concluding that it applies only when prospective parents have already engaged in the in vitro fertilization process.